Kampo herbal ointments for skin wound healing - Paul-Traversaz, Manon; Umehara, Kaoru; Watanabe, Kenji; Rachidi, Walid; Sève, Michel; Souard, Florence (Frontiers in Pharmacology, 2023)
The management of skin wound healing problems is a public health issue in which traditional herbal medicines could play a determining role. Kampo medicine, with three traditionally used ointments, provides interesting solutions for these dermatological issues. These ointments named Shiunkō, Chuōkō and Shinsen taitsukō all have in common a lipophilic base of sesame oil and beeswax in which herbal crude drugs are extracted according several possible manufacturing protocols. This review article brings together existing data on metabolites involved in the complex wound healing process. Among them, are representatives of the botanical genus Angelica, Lithospermum, Curcuma, Phellodendron, Paeonia, Rheum, Rehmannia, Scrophularia or Cinnamomum. Kampo provides numerous metabolites of interest whose content in crude drugs is very sensitive to different biotic and abiotic factors as well as to the different extraction protocols used for these ointments. If Kampo medicine is known for its singular standardization, ointments are not well known and research on these lipophilic formulas is not developed due to the analytical difficulties encountered in biological and metabolomic analysis. Further research taking into account the complexities of these unique herbal ointments could contribute to a rationalization of the Kampo therapeutic uses for wound healing.